Homophobic conceptions of high school students - Rondini, Carina Alexandra [UNESP]; Filho, Fernando Silva Teixeira; Toledo, Lívia Gonsalves [UNESP] (FapUNIFESP (SciELO), 2017)
This paper presents the results of a study carried on with 2,159 male and female high school students from three cities in the countryside of São Paulo State, Brazil. The data obtained by a Likert scale were analyzed by a multivariate statistical technique. Regarding the factor analysis, the method used for extracting the factors was the major component and oblique rotation method, in which the six factors obtained aid to interpreting the possible correlations among the homophobic views presented in items. The study revealed that moderate tolerance for gay, lesbian and transgender people in this young sample is a reality that needs attention of public policies in education targeting strategies for the deconstruction of gender stereotypes and eradication of homophobia, lesbophobia and transphobia among adolescents.
Keywords: Adolescents; Factor analysis; Homophobia; Homophobic conceptions; School